Work Calling: Exploring the Communicative Intersections of Meaningful Work and Organizational Spirituality. Issue 3 (26th May 2016) - Molloy, K. Arianna; Foust, Christina R.
Abstract : In the present study, we first describe three themes from the interdisciplinary literature: sacred and secular variations; calling as historically and culturally situated; and potential benefits, alienation, and marginalization. Second, through a thematic analysis (Owen, 1984) based on participant data, we examine how participants' understanding and interpretation of work calling as an overarching meaningfulness, a combination of personal passion and skill set, and a contribution to society serve as definitional makers. We argue that these findings emphasize the processural and constitutive nature of work calling. We conclude by highlighting the communicative dimensions of work calling as they may contribute to future critical and empirical work, noting the possibilities for sense-making theory to intervene in this interdisciplinary area of inquiry.